2023
DOI: 10.3390/ijms24032153
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Vegetable Oil-Based Biomaterials: Synthesis and Biomedical Applications

Abstract: One of the main criteria for ecological sustainability is that the materials produced for common use are green. This can include the use of biomaterials and materials that are environmentally friendly, biodegradable and produced at low cost. The exploration of natural resources as sustainable precursors leads to the production of biopolymers that are useful for 3D printing technology. Recently, waste vegetable oils have been found to be a good alternative source for the production of biopolymers in various app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…However, sustainability applies not only to nanoparticles but also to the base oil for comprehensive nano-lubricant production. Biomaterials based on vegetable oils offer a sustainable, biodegradable and low-cost alternative for various applications in engineering and biomedicine [191]. Taha-Tijerina et al found that halloysite nanotubular structures (HNSs) reinforcing natural ester lubricants significantly reduce the friction coefficient and wear scar diameter, offering environmentally friendly alternatives to mineral fluids for industrial applications [192].…”
Section: Base Lubricantsmentioning
confidence: 99%
“…However, sustainability applies not only to nanoparticles but also to the base oil for comprehensive nano-lubricant production. Biomaterials based on vegetable oils offer a sustainable, biodegradable and low-cost alternative for various applications in engineering and biomedicine [191]. Taha-Tijerina et al found that halloysite nanotubular structures (HNSs) reinforcing natural ester lubricants significantly reduce the friction coefficient and wear scar diameter, offering environmentally friendly alternatives to mineral fluids for industrial applications [192].…”
Section: Base Lubricantsmentioning
confidence: 99%
“…Photocurable resins used in light-curing 3D printing require several important characteristics, including high curing rate, stable storage performance, low viscosity, low toxicity, and good mechanical properties [4][5][6] . To date, a wide range of photocurable resins has been documented for 3D printing, primarily utilizing prepolymers derived from petroleum-based acrylates [7,8] , acrylamides [9,10] , or ethylene glycols [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, different types of acrylates, such as polyethylene glycol diacrylate (PEGDA), are incorporated in VO-based acrylates to develop hybrid resins, adjusting their viscosity to match the requirements of specific 3D printers. 12 Furthermore, to replicate the mechanical properties of synthetic resins, composite resins containing fillers as reinforcements have also been introduced in the 3D printing materials market. 13 However, despite these developments, the 3D printing of bio-based polymers derived from plant-based oils remains unexplored and necessitates comprehensive scientific research.…”
Section: Introductionmentioning
confidence: 99%